Investigating the Dynamic of Halal Food Certification Adoption: Necessity or Opportunity? - Retty Ikawati; Boyke R Purnomo (BASKARA : Journal of Business and Entrepreneurship, 2025)
The largest Muslim population globally, Indonesia has emerged as a prospective area for the growth of the halal food industry. Obtaining halal food certification not only assures adherence to  sharia law for Muslim consumers but also enhances the competitiveness of the producers. Despite suggesting various benefits, in Indonesia, the adoption rate of halal food certification remains quiet low, approximately ten percent. Moreover, the literature also discusses little how food manufacturers adopt halal certification. This study aims to investigate the dynamics of the adoption process of halal food certification. To achieve this objective, the exploratory research relies on a questionnaire based method designed within a posituve approach. Initially, the researchers conducted a questionaire to ninety-eight Yogyakarta-based SMEs to identify their entrepreneurial orientation and intention to adopt halal food certification, then it continued with in-depth interviews with eight informants to explore the motives and patterns of the adoption of halal certification. The findings reveal that the motivations related to entrepreneurship align with the method of halal certification adoption. Additionally, the choice to adopt halal certification was primarily driven by a necessity to adhere to regulations mandating halal certification. The study also highlights that SMEs’ assumptions concerning readiness for administrative, financial support, and limited information access are significant factors influencing their decision to adopt halal certification.